KADAR FIBRINOGEN SEBAGAI FAKTOR PROGNOSTIK PASIEN PERDARAHAN INTRASEREBRAL SPONTAN - David Tandian,* Muhammad Harisyah,* Hanif Gordang Tobing,* Samsul Ashari,* Renindra Ananda Aman,* Sy (NEURONA, 2018)
INTRODUCTION SPONTANEOUS INTRACEREBRAL HAEMORRHAGE SIH REFERS AS SPONTANEOUS BLEEDING IN THE BRAIN PAREN CHYMA DUE TO INJURY OF BLOOD VESSELS THUS CAUSING TISSUE INFLAMMATORY AND COAGULATION REACTION ACTIVATING THE RELEASE OF FIBRINOGEN FIBRINOGEN AN ACTIVE SUBSTRATE OF COAGULATION CASCADE ALSO CONSIDERED AS THE MOST POWERFUL INDICATOR OF ACUTE INFLAMMATORY RESPONSE IN SIH ELEVATED LEVELS OF FIBRINOGEN MAY BE THE MARKER FOR THE INCREASING DEGREE OF BRAIN TISSUE DAMAGE